2011
DOI: 10.1628/093245611796589915
|View full text |Cite
|
Sign up to set email alerts
|

Repayment versus Investment Conditions and Exclusivity in Lending Contracts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Extensions that address this issue would evidently be in order. Lastly,Bougheas et al (2011) have shown, in the context of international lending, that conditionalities imposed on borrowers may be inefficient in the presence of multiple, competing lenders. The issue of whether competition among multiple donors, for the services of a given pool of NGOs, may likewise affect and qualify the optimal approach to NGO regulation, constitutes another important line of future enquiry suggested by this paper.12 SeeGuriev (2004),Bardhan (1997),Mookherjee and Png (1995) andShleifer and Vishny (1993).13 Bougheas et al (2007) show, in the general context of charitable donations, that widely popular donor conditionalities may be inefficient, yet persist indefinitely.…”
mentioning
confidence: 99%
“…Extensions that address this issue would evidently be in order. Lastly,Bougheas et al (2011) have shown, in the context of international lending, that conditionalities imposed on borrowers may be inefficient in the presence of multiple, competing lenders. The issue of whether competition among multiple donors, for the services of a given pool of NGOs, may likewise affect and qualify the optimal approach to NGO regulation, constitutes another important line of future enquiry suggested by this paper.12 SeeGuriev (2004),Bardhan (1997),Mookherjee and Png (1995) andShleifer and Vishny (1993).13 Bougheas et al (2007) show, in the general context of charitable donations, that widely popular donor conditionalities may be inefficient, yet persist indefinitely.…”
mentioning
confidence: 99%